Daring to fall for the prince - Helmy, Heba (Helmy, Heba. Princes of Egypt., 2025)
"When Elise agrees to pose as her friend Lady Olive in a few letters with a faraway prince, she never dreams she'll actually meet the man. Yet when they travel from England to Egypt, and Olive runs away, Elise finds herself alone with Prince Saleem and fighting a forbidden attraction. It might be a tactical match, but Saleem's all but betrothed to her best friend, and fiercely independent Elise is wary of his royal world. As they team up to solve a dangerous mystery, dare Elise reveal she's the one who wrote the letters and surrender to this impossible desire?"--